Molecular cloning and sequence analysis of an inulinase gene from an endophytic fungus - Shamsuddin, Raba’atun Adawiyah (2010)
Endophytes, by definition, are organisms including fungi that live in close association with living plant tissues. Since no plants without endophytic fungi have been found to date, it is considered that endophytic fungi in plants are a common and general phenomenon. However, very few microorganisms living in plants were reported to be inulin degraders. Inulin occurs as a reserve carbohydrate in plants. Depolymerization of inulin involves the action of inulinase enzymes, isolated from microorganisms including fungi. In this study, the endophytes producing inulinase were isolated from plant species in Serdang area. Thus, the fungal isolates were screened for inulin degrading enzymes. The results were evaluated in terms of substrate consumption and cell growth. All fungal isolates were able to degrade inulin and, among these, two isolates, named Asf1 and Onf1, were selected as the best inulinase producers. Genomic DNA of all isolates were extracted and amplified by polymerase chain reaction (PCR). A 1341 bp DNA fragment containing inulinase gene was successfully amplified from Asf1 fungal isolate and was named as inu2 gene in this study. Based on the morphological characteristics, Asf1 fungal isolate display closely-related to that genus of Aspergillus. The 18S ribosomal DNA sequence analysis revealed their high similarity of 99% to those of Aspergillus species. According to the neighbor-joining phylogenetic tree, Asf1 fungal isolate was shown to be closest to the species from the genus Aspergillus. The complete sequence designated Asf1 inu2 gene, was successfully obtained via rapid-amplification of cDNA ends-polymerase chain reaction (RACE-PCR). A 2.3 kb DNA fragment encoding endoinulinase, inu2, from Asf1 fungal isolate includes an open reading frame of 1,552 bp with calculated molecular weight of 55954.1 Da and signal peptide sequence of 23 amino acids. The deduced amino acid sequence of the Asf1 Inu2 showed 97%, 96%, 69% and 22% identities to that of A. ficuum inu2, A. niger inuB, P. purpurogenum and K. marxianus, respectively. A phylogenetic analysis showed that fungal endo- and exo-inulinases have indepently evolved the respective hydrolytic activities toward terminal and internal β-(2→1)-fructofuranosidic linkages in inulin.